2022
DOI: 10.1051/matecconf/202235708001
|View full text |Cite
|
Sign up to set email alerts
|

The Algebraic Model of the Dry Ice Extrusion Process in a Die with a Conical-Cylindrical Channel

Abstract: The article presents the results of works on formulating an algebraic model of crystallized CO2 extrusion process in a convergent circular–symmetrical channel. The paper presents the method of derivation of the model as well as preliminary comparison of the influence of variance of the 3 geometrical parameters describing the shape of the forming channel. Based on the results of the performed analysis, conclusions are formulated to determine the basis and future direction of study to the development of single-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Along with the development of the concept of a new type of calorimeter, it was decided to make a mathematical model that would be its theoretical reflection. This gives endless possibilities in the field of testing the truthfulness of the assumptions used in the concept of the device, and later, after making a prototype of the calorimeter, it allows to check the reliability of the obtained results [7]. The SciLab software has been used to perform this task, and the model, depending on the calculated physical quantity, has been shown in figures 2, 3 and 4 [8].…”
Section: Numerical Modelmentioning
confidence: 99%
“…Along with the development of the concept of a new type of calorimeter, it was decided to make a mathematical model that would be its theoretical reflection. This gives endless possibilities in the field of testing the truthfulness of the assumptions used in the concept of the device, and later, after making a prototype of the calorimeter, it allows to check the reliability of the obtained results [7]. The SciLab software has been used to perform this task, and the model, depending on the calculated physical quantity, has been shown in figures 2, 3 and 4 [8].…”
Section: Numerical Modelmentioning
confidence: 99%
“…This results in friction between the compressed material and the compression cavity walls, increasing the compression resistance. The dissipation of energy during compression, in cylindrical chambers with tapered ends, has been extensively described in the literature [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The value of force F e increases until it equals the maximum resistance force of the process of compression F L . It has been demonstrated that the value of this force depends on the die parameters and the coefficient of friction between the extruded material and the side walls of the die [18]. The value of F e decreases as the process of extrusion proceeds and the density of the material ρ no longer increases as a result [20].…”
Section: Introductionmentioning
confidence: 99%